Overlapping Primary and Secondary Syphilis in a Bisexual Patient with Human Immunodeficiency Virus - Lita Setyowatie; Wika Umayatul Choiroh (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: Syphilis and HIV are diseases that can be transmitted through sexual contact. Bisexual groups have a higher potential for HIV and syphilis transmission. In syphilis patients who have been infected with HIV, secondary syphilis often occurs along with primary syphilis, which can be found 2-3 times more often than in those who are not infected by HIV. Case: A 24-year-old male with HIV who is a bisexual man, complained chancre on his scrotum and on the tip of the penis that was painless and also has condyloma lata around the anus. Dermatological examination revealed multiple papules, patches, and plaques. The serological results for VDRL and TPHA were reactive. Histopathology examination of skin plaque suggests secondary syphilis. The Patient was diagnosed with overlapping primary-secondary syphilis and given therapy with single-dose intramuscular injection of benzathine penicillin G. Discussion: Bisexual groups have a higher potential for HIV and syphilis transmission. In HIV patients, primary and secondary syphilis often overlap. This was due to changes in the immune system causing the spread of Treponema pallidum more quickly and slowing the healing of primary lesions. Conclusion: Overlapping of primary and secondary syphilis in bisexual patients with HIV is common; in addition, the appearance of skin lesions in secondary syphilis can resemble other diseases, so confirmation by histopathology examination needs to be done.